2007
DOI: 10.1136/hrt.2006.097477
|View full text |Cite
|
Sign up to set email alerts
|

Trimetazidine in the prevention of contrast-induced nephropathy after coronary procedures

Abstract: Objective: To evaluate the efficacy of trimetazidine (TMZ) in the prevention of contrast-induced nephropathy (CIN) in patients with high serum creatinine levels undergoing coronary angiography/angioplasty. Methods: TMZ (20 mg thrice daily) was administered orally for 72 h starting 48 h before the procedure. All patients were given intravenous saline (0.9%) at a rate of 1 ml/kg of body weight per hour for 24 h starting 12 h beforehand. Serum creatinine levels were measured before the procedure, 48 h and 7 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
2
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 56 publications
5
40
2
5
Order By: Relevance
“…24 Recently, Onbaşılı et al were the first to report that TMZ-a cellular anti-ischemic agent-was effective in preventing CIN in patients undergoing coronary procedures. 9 Moreover, Rahman et al confirmed those findings in a study that included 400 patients undergoing coronary angiography; 25 however, neither study was able to identify the physiopathological mechanism of action or was designed to include histopathological findings. As such, the present study aimed to histopathologically analyze the effect of TMZ in preventing CIN and to identify the probable biochemical mechanism of action.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…24 Recently, Onbaşılı et al were the first to report that TMZ-a cellular anti-ischemic agent-was effective in preventing CIN in patients undergoing coronary procedures. 9 Moreover, Rahman et al confirmed those findings in a study that included 400 patients undergoing coronary angiography; 25 however, neither study was able to identify the physiopathological mechanism of action or was designed to include histopathological findings. As such, the present study aimed to histopathologically analyze the effect of TMZ in preventing CIN and to identify the probable biochemical mechanism of action.…”
Section: Discussionsupporting
confidence: 53%
“…19 Additionally, these free radicals are thought to cause apoptosis in renal tubule and glomerular cells. 9 Sandhu et al reported earlier that the urinary MDA/creatinine ratio increased following CM infusion and that there might be a relationship between CM infusion and free radical generation. 20 The present study's findings are in agreement with these data, as the MDA level significantly increased and SOD activity significantly decreased after administration of CM in the CM group, as compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Trimetazidine or (1-2(2,3,4-trimeoxibenzyl)-piperazine) (TMZ), is used as an anti-anginal agent, selectively inhibits long-chain 3-ketoacyl coenzyme A thiolase (the last enzyme involved in b-oxidation) activity. 9 Its anti-ischemic effects on the kidney have been experimentally assessed in various models including cell culture 10 isolated and perfused kidneys 11 and in vivo. 12,13 TMZ has different pharmacological properties that could be relevant for the prevention of organ damage from I/R by reduction of intracellular acidosis, 14 preservation of ATP production, limitation of inflammatory reaction, and thus of ROS generation.…”
Section: Introductionmentioning
confidence: 99%
“…Ряд экспериментальных и клинических исследований позволяют предполагать наличие у триметазидина нефро-протективного эффекта [78][79][80][81][82]. Например, при назначе-нии триметазидина МВ за 2 дня до проведения инвазив-ных коронарных процедур (коронарография и др.)…”
Section: на сегодняшний день обсуждаются плейотропные эффекты триметаunclassified